2022
DOI: 10.3390/nu14193883
|View full text |Cite
|
Sign up to set email alerts
|

Protein Supplementation Does Not Maximize Adaptations to Low-Volume High-Intensity Interval Training in Sedentary, Healthy Adults: A Placebo-Controlled Double-Blind Randomized Study

Abstract: There is ample evidence that specific nutritional strategies can enhance adaptions to resistance and endurance training. However, it is still unclear whether post-session protein supplementation may increase the effects of low-volume high-intensity interval training (LOW-HIIT). We examined the impact of LOW-HIIT combined with protein vs. placebo supplementation on cardiometabolic health indices in sedentary healthy individuals. Forty-seven participants (31.1 ± 8.0 yrs) performed cycle ergometer LOW-HIIT (5–10x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…However, drinking coffee for two weeks did not seem to increase blood pressure. Previous research has shown conflicting findings regarding the relationship between blood pressure and coffee and caffeine consumption 17 . Randomized controlled trials have indicated that short-term consumption of caffeine or coffee leads to an immediate elevation of 2/1 mm Hg in systolic and diastolic blood pressure compared to decaffeinated coffee or abstention 18 .…”
Section: Discussionmentioning
confidence: 98%
“…However, drinking coffee for two weeks did not seem to increase blood pressure. Previous research has shown conflicting findings regarding the relationship between blood pressure and coffee and caffeine consumption 17 . Randomized controlled trials have indicated that short-term consumption of caffeine or coffee leads to an immediate elevation of 2/1 mm Hg in systolic and diastolic blood pressure compared to decaffeinated coffee or abstention 18 .…”
Section: Discussionmentioning
confidence: 98%
“…It can be consumed exogenously and is found in high concentrations in wheat germ and other vegetables [128,129], though conflicting information exists on whether supplementation raises polyamine levels. Studies show that oral polyamine intake raises levels [130,131] supplementation does not appear to raise spermidine levels [132]. However, spermidine supplementation shows improvement in cognitive function in animal models [133].…”
Section: Spermidinementioning
confidence: 99%